2015
DOI: 10.1063/1.4914475
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar resistive switching in planar Pt/BiFeO3/Pt structure

Abstract: We report unipolar resistive switching suitable for nonvolatile memory applications in polycrystalline BiFeO 3 thin films in planar electrode configuration with nonoverlapping Set and Reset voltages, On/Off resistance ratio of ∼10 4 and good data retention (verified for up to 3,000 s). We have also observed photovoltaic response in both high and low resistance states, where the photocurrent density was about three orders of magnitude higher in the low resistance state as compared to the high resistance state a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 25 publications
4
9
0
Order By: Relevance
“…We have also measured the temperature-dependent resistance variation of the ReRAM device; the results showed that the resistance increases upon increasing the measuring temperature in the LRS (not shown here), which proves that the filament is really composed of metal ions. The same results are also reported in literature [ 18 , 19 , 20 ].…”
Section: Resultssupporting
confidence: 90%
“…We have also measured the temperature-dependent resistance variation of the ReRAM device; the results showed that the resistance increases upon increasing the measuring temperature in the LRS (not shown here), which proves that the filament is really composed of metal ions. The same results are also reported in literature [ 18 , 19 , 20 ].…”
Section: Resultssupporting
confidence: 90%
“…In recent photovoltaic studies , BFO thin films and crystals with various electrodes have shown properties with potential for PV applications. Pt/BFO/SRO and Pt/Sm:BFO/SRO thin films heterostructures showed significantly higher PV current densities in the lowresistance state under white-light illumination [30,31]. BFO has been considered a p-type semiconducting material resulting from the Bi 3+ loss during the sintering process, which causes vacancies to act as p-type centers [42].…”
Section: Introductionmentioning
confidence: 99%
“…The retention of the resistive switching states was tested to confirm the applicability, as the long-term retention of HRS LRS is an important factor in ReRAM [15]. As a result, the retention capability of the structure was investigated further by monitoring the states at a read voltage of +0.5 V [7].…”
Section: Resultsmentioning
confidence: 99%